Lithium batteries and other electrochemical storage systems - Glaize, Christian; Genies, Sylvie (Hoboken : Wiley ; London : ISTE, 2013)
Lithium batteries were introduced relatively recently in comparison to lead- or nickel-based batteries, which have been around for over 100 years. Nevertheless, in the space of 20 years, they have acquired a considerable market share - particularly for the supply of mobile devices. We are still a long way from exhausting the possibilities that they offer. Numerous projects will undoubtedly further improve their performances in the years to come. For large-scale storage systems, other types of batteries are also worthy of consideration: hot batteries and redox flow systems, for example.
Chapter 4. Introduction to Lithium Batteries; 4.1. History of lithium batteries; 4.2. Categories of lithium batteries; 4.3. The different operational mechanisms for lithium batteries; 4.3.1. Intercalation (or insertion) materials; 4.3.2. Alloys; 4.3.3. Direction conversion materials; 4.3.4. Differences of voltage profiles between intercalation materials, alloys and conversion materials; 4.3.5. Properties of the electrode materials.
Online resource; title from PDF title page (Wiley, viewed August 26, 2013).
Keywords: Lithium cells; Battery separators; Electric batteries; Lithium-sulfur batteries; TECHNOLOGY & ENGINEERING -- Mechanical; Lithium cells; Electronic books